Assessment of potential health risk association with ingesting heavy metals in oreochromis niloticus collected from selected area in Kepong, Kuala Lumpur / Mohd Shahrir Mahmud Zuhdi - Mahmud Zuhdi, Mohd Shahrir (2012)
Recently, heavy metal pollutions in aquatic ecosystem are becoming critical issues. Bioaccumulation of heavy metals in aquatic animals causes serious threat to the human health when they are consumed. This study was conducted to determine the concentration of heavy metals (Pb and Cd) in muscle tissues, gills and bones of of Oreochromis niloticus (black tilapia) which was collected from two selected location around Kepong area, Kuala Lumpur and its potential human health risk. The sites included a Sri Murni Pond and Kepong Metropolitan Lake, that nearby with Taman Beringin ex-landfill. Metals concentration in fish organs were measured using dry ashing acid digestion method and be analyzed by atomic absorption spectrophotometer (AAS) AA 800 model Perkin Elmer. The results obtained shows that the highest concentrations for lead (Pb) were detected in the gill followed by bones and the least in muscle tissues. Based on the post hoc test, it has been proved that there is a lead (Pb) significant between the organs where there is a mean different between "Muscle and Gills" and "Muscle and Bones" pairs since (p<0.05). For Cadmium (Cd), most metal is accumulated in the bone compared to gill and muscle tissues. Besides, only 'Bones and Gills" and "Bones and Muscle" pairs are significantly different by post-hoc test Scheffe's procedures (p<0.05). Heavy metals concentration in fish organ collected from both sites were within the maximum allowable limits when compared to the Fourteenth Schedule of the Malaysian Food Regulations 1985. For the potential health risk, the Hazard Index (HI) for both heavy metals only focused on the muscle tissue rather than gill and bone. Since the HI are less than 1 (Hl<1 ), it means a consumption of muscle tissue may not pose as a threat to human health and are completely known to be safe to be consumed by humans.